Extraversion, Conscientiousness and Intrinsic Motivation Towards Happiness in Malaysia: Perspective of Malaysian Business Students in Private University - Fauzi, Muna Wadhiha Mohd; Hussein, Norashikin; Razali, Murni Zarina Mohamed; Anwar, Nur Aizureen; Omar, Norhayati (Advances in Social Sciences Research Journal, 2023)
Modern society now uses happiness as one of the primary indicators of social advancement. Happiness is vital to the energetic millennial generation, especially for university students. As a result, the first goal of this study is to ascertain the relationship between extraversion and happiness. The second goal is to ascertain the relationship between conscientiousness and happiness in Malaysia. The third goal is to ascertain the relationship between intrinsic motivation and happiness. 120 business faculty students in a private institution in Malaysia who were enrolled in bachelor's degree programmes received online surveys. A "Likert-type scale" was used to determine the degree of agreement or disagreement with relation to happiness using the Subjective Happiness Scale (SHS). All of the questions were created to be closed-ended for simple analysis of the feedback. The results of the study demonstrated a positive, statistically significant relationship between happiness and the three independent variables of extraversion, conscientiousness, and intrinsic motivation. This study also sheds light on providing extracurricular activities that can increase students' happiness.